Upregulated Expression of SOX4 Is Associated with Tumor Growth and Metastasis in Nasopharyngeal Carcinoma. (22nd October 2015) - Shi, Si; Cao, Xiaolei; Gu, Miao; You, Bo; Shan, Ying; You, Yiwen
Abstract : SOX4, which belongs to the sex-determining region Y-related high-mobility group (SRY) box family, plays a critical role in embryonic development, cell fate decision, differentiation, and tumor development. Nasopharyngeal carcinoma (NPC) is one of the most common cancers in China and Southeast Asia. However, the molecular mechanisms of this disease remain unknown. In the present study, we used immunohistochemistry to investigate the correlation between the expression of SOX4 with clinicopathologic variables as well as patients prognosis of NPC. We found overexpression of SOX4 was correlated with clinical stages, lymph node metastasis, and Ki-67 expression in NPC (P < 0.05 ). Besides, patients who expressed higher levels of SOX4 had poorer survival rate (P < 0.05 ). Then, in vitro studies, we took serum starvation-refeeding experiment and knocked down the expression of SOX4 with siRNA to demonstrate that SOX4 could promote proliferation of NPC nonkeratinizing cell line CNE2. The regulation of SOX4 on cell migration was determined by the transwell migration assay and wounding healing assay. Besides, we also found SOX4 could promote epithelial-mesenchymal transition (EMT) of CNE2 cells and decrease their cisplatin sensitivity. Our data suggested that SOX4 might play an important role in regulating NPC progression and would provide a potential therapeutic strategy for NPC.